2018
DOI: 10.3390/rs10060833
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Performances of Radar Altimetry Missions from ERS-2 to Sentinel-3A over the Inner Niger Delta

Abstract: Radar altimetry provides unique information on water stages of inland hydro-systems. In this study, the performance of seven altimetry missions, among the most commonly used in land hydrology (i.e., European Remote-Sensing Satellite-2 (ERS-2), ENVIronment SATellite (ENVISAT), Satellite with Argos and ALtika (SARAL), Jason-1, Jason-2, Jason-3 and Sentinel-3A), are assessed using records from a dense in situ network composed of 19 gauge stations in the Inner Niger Delta (IND) from 1995 to 2017. Results show an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 54 publications
5
58
0
Order By: Relevance
“…Time series of water levels based on the ICE-1 retracked ranges which provides accurate estimate of the height of the lake water bodies 56 , were derived using the Multi-mission Altimetry Processing Software (MAPS), that is commonly used for this purpose 58,59 . Details of the processing of the altimetry data in MAPS can be found in Normandin et al 60 . As already mentioned, only altimetry data from the 35-day repeat period missions are used, meaning that there are 11 values of water level per year per VS.…”
Section: Methodsmentioning
confidence: 99%
“…Time series of water levels based on the ICE-1 retracked ranges which provides accurate estimate of the height of the lake water bodies 56 , were derived using the Multi-mission Altimetry Processing Software (MAPS), that is commonly used for this purpose 58,59 . Details of the processing of the altimetry data in MAPS can be found in Normandin et al 60 . As already mentioned, only altimetry data from the 35-day repeat period missions are used, meaning that there are 11 values of water level per year per VS.…”
Section: Methodsmentioning
confidence: 99%
“…We also use data from the Sentinel‐3A satellite that became operational in 2016. There is less than 3 years of data at the time of writing, and performance evaluation is limited, although a recent study on the Niger River reported improved performance of Sentinel‐3A compared with well‐established altimeters including ENVISAT (Normandin et al, ). However, it was operational during our field campaign so is of use for comparative purposes.…”
Section: Methods and Data Setsmentioning
confidence: 99%
“…The IRWR data for Africa were acquired from the AQUASTAT database at (http://www.fao.org/nr/water/aquastat/data/query/index.html?lang=en). The lake level altimetry observations for four major African Lakes (Tana, Victoria, Malawi, and Tanganyika) and two reservoirs (Volta and Nasser) were obtained from the HYDROWEB portal (http://hydroweb.theia-land.fr/); noteworthy, these lake level altimetry observations have good agreement with in-situ water levels observations according to [37,53]. Additionally, through personal communications, we acquired the time series for the depth to groundwater for twenty observational wells in North Ghana from December 2005 to December 2012.…”
Section: Ancillary Datamentioning
confidence: 96%